BUSINESS STRATEGY, INTELLECTUAL CAPITAL, BOARD INDEPENDENCE ON BANKRUPTCY RISK - Pratiwi, Ika; Permana, Aryo Bimo Setya (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
This study provides empirical data on the factors influencing bankruptcy risk companies in Indonesia. Bankruptcy risk is a critical issue that threatens corporate sustainability, especially in highly competitive and uncertain business environments. Internal factors such as the effective utilization of intellectual capital, the implementation of appropriate business strategies, and the strength of corporate governance through board independence are believed to influence the likelihood of bankruptcy. Intellectual Capital, Business Strategy, Board Independence are used as independent variables. The dataset consists of non-financial companies listed on the Indonesia Stock Exchange, covering the period from 2023 to 2024. The sampling using purposive sampling. There are 484 data that included the criteria. Multiple regression analysis used to be technique analysis. The results indicate that business strategy and board independence has a significant negative effect, while intellectual capital shows insignificant impact on bankruptcy risk. The results underscore the significance of incorporating strategic resources and governance mechanisms to strengthen corporate sustainability and ensuring financial stability. This research adds to the body of literature on bankruptcy prediction by incorporating non-financial determinants and governance dimensions, and provides practical implications for managers and regulators seeking to enhance firm resilience through improved intellectual capital management, strategic alignment, and board independence.